A Clustered Multiclass Likelihood‐Ratio Ensemble Method for Family‐Based Association Analysis Accounting for Phenotypic Heterogeneity. Issue 6 (19th June 2016) - Wen, Yalu; Lu, Qing
ABSTRACT: Although compelling evidence suggests that the genetic etiology of complex diseases could be heterogeneous in subphenotype groups, little attention has been paid to phenotypic heterogeneity in genetic association analysis of complex diseases. Simply ignoring phenotypic heterogeneity in association analysis could result in attenuated estimates of genetic effects and low power of association tests if subphenotypes with similar clinical manifestations have heterogeneous underlying genetic etiologies. To facilitate the family‐based association analysis allowing for phenotypic heterogeneity, we propose a clustered multiclass likelihood‐ratio ensemble (CMLRE) method. The proposed method provides an alternative way to model the complex relationship between disease outcomes and genetic variants. It allows for heterogeneous genetic causes of disease subphenotypes and can be applied to various pedigree structures. Through simulations, we found CMLRE outperformed the commonly adopted strategies in a variety of underlying disease scenarios. We further applied CMLRE to a family‐based dataset from the International Consortium to Identify Genes and Interactions Controlling Oral Clefts (ICOC) to investigate the genetic variants and interactions predisposing to subphenotypes of oral clefts. The analysis suggested that two subphenotypes, nonsyndromic cleft lip without palate (CL) and cleft lip with palate (CLP), shared similar genetic etiologies, while cleft palate only (CP) had its own genetic mechanism. The analysis further revealed that rs10863790 ( IRF6 ), rs7017252 ( 8q24 ), and rs7078160 ( VAX1 ) were jointly associated with CL/CLP, while rs7969932 ( TBK1 ), rs227731 ( 17q22 ), and rs2141765 ( TBK1 ) jointly contributed to CP.